2013
DOI: 10.1017/s0031182013001765
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationship ofHepatozoonblood parasites found in snakes from Africa, America and Asia

Abstract: The blood parasites from the genus Hepatozoon Miller, 1908 (Apicomplexa: Adeleida: Hepatozoidae) represent the most common intracellular protozoan parasites found in snakes. In the present study, we examined 209 individuals of snakes, from different zoogeographical regions (Africa, America, Asia and Europe), for the occurrence of blood parasites using both molecular and microscopic examination methods, and assess phylogenetic relationships of all Hepatozoon parasites from snakes for the first time. In total, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Hepatozoon sipedon, for example, is known to naturally infect the snake, Nerodia sipedon sipedon, through the ingestion of an anuran, Rana pipiens (Schreber) (Smith 1994, Netherlands et al 2014a). Furthermore, these non-ophidian intermediate host associations are becoming evident in the phylogenetic analyses of species of Hepatozoon because species infecting snakes with a diet comprising mostly anurans and those with a diet comprising mostly saurians belong to separate lineages (Haklová et al 2014). Tomé et al (2013) demonstrated that diet appears to be a key element for infection of snakes by species of Hepatozoon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hepatozoon sipedon, for example, is known to naturally infect the snake, Nerodia sipedon sipedon, through the ingestion of an anuran, Rana pipiens (Schreber) (Smith 1994, Netherlands et al 2014a). Furthermore, these non-ophidian intermediate host associations are becoming evident in the phylogenetic analyses of species of Hepatozoon because species infecting snakes with a diet comprising mostly anurans and those with a diet comprising mostly saurians belong to separate lineages (Haklová et al 2014). Tomé et al (2013) demonstrated that diet appears to be a key element for infection of snakes by species of Hepatozoon.…”
Section: Discussionmentioning
confidence: 99%
“…It is unfortunate that the species of Hepatozoon parasitising P. semivariegatus from Swaziland sequenced by Haklová et al (2014) could not be compared on a morphological basis to H. angeladaviesae and H. cecilhoarei. Furthermore, as the fragment used in the evolutionary divergence estimates represents a relatively conservative section of the 18S rRNA gene, results may demonstrate a closer relatedness than what is truly the case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[81] Protozoa Hepatozoon ayorgbor [84], Hepatozoon spp. [84][85][86], Trypanosoma cf. varani [87], Trypanosoma spp.…”
Section: Bacteriamentioning
confidence: 99%